THE INFLUENCE OF REGIONAL MINIMUM WAGE ON POVERTY IN JAMBI CITY: A MODERATING ROLE OF THE OPEN UNEMPLOYMENT RATE - Adi Putra; Faradilla Herlin (Jurnal Development, 2025)
This study aims to analyze the effect of the Regional Minimum Wage (RMW) on poverty levels in Jambi City, considering the Open Unemployment Rate (OUR) as a moderating variable. A quantitative approach was employed, using secondary data obtained from the Central Statistics Agency (BPS) of Jambi City for the period 2013–2022. Data were analyzed using simple regression and Moderated Regression Analysis (MRA) with the assistance of SPSS software. The results show that the direct effect of RMW on OUR is very low, with an R² value of 0.031, indicating that only 3.1% of the variation in unemployment is explained by RMW. However, after including inflation as a moderating variable, the R² value significantly increased to 0.727, suggesting that inflation substantially strengthens the relationship between RMW and OUR. These findings imply that minimum wage policies alone are not sufficiently effective in reducing unemployment without being complemented by other factors such as inflation control, economic growth, and workforce quality. Furthermore, the study finds that the inflation trend in Jambi City during the period was relatively stable, averaging 3.24%, despite significant fluctuations in certain years, such as 2014 and 2020. This inflation stability plays a vital role in maintaining purchasing power and labor market equilibrium. Therefore, local governments should not rely solely on raising minimum wages as a singular strategy but must also enhance vocational training programs, improve workforce skills, and create productive employment opportunities aligned with local industry demands.